Designing an ecotourism initiative to create economic incentives for forest conservation/ Huda Farhana MM and Mohd Parid M - MM, Huda Farhana; M, Mohd Parid (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Forest reserves and protected areas have significant ability as the effective nature conservation strategies especially in conserving forest habitats. Many alternatives were developed to improve habitat destruction in forest environments, including empowerment of local communities' participation. The research aims to create financial incentives to strengthen the local community's involvement using conservation financing approach in ecotourism strategies at Ulu Tampik Waterfall (UTW), Lentang Forest Reserve, Bentong, Pahang. It also discusses strategies adopted in empowering locals for ecotourism purposes by implication conserving the forest reserve for Primary data and baseline information were collected through rapid rural appraisal, focus group discussion and field research to estimate the economic benefits of preserving the forest area based on public preferences. It examined 149 respondents (January 2018) to estimate willingness to pay (WTP) for natural resource conservation using the contingent valuation method (CVM). A few initiatives also were adopted to empower local community including stakeholders' consultation workshops, technical visits and study tours to Malaysia's best practices community-based ecotourism from 2018 to the latest event in 2021. Such programmes indirectly educate and empower local community's knowledge, experience and support in natural resource conservation.